Ultrafine porous boron nitride nanofiber‐toughened WC composites. Issue 3 (22nd January 2020) - Li, Xiaoqiang; Cao, Ting; Zhang, Minai; Qiu, Hao; Huang, Yang; Qu, Shengguan; Liang, Liang; Song, Tao
Abstract: Porous fibers are widely used in catalysis chemistry and hydrogen storage but are rarely used in structural ceramics. In this study, spark plasma sintering was used to prepare an ultrafine porous boron nitride nanofiber‐toughened WC composite for the first time. The obtained WC‐0.05 wt% ultrafine porous boron nitride nanofiber composites exhibited better properties (ie, a 2.3% increase in hardness and a 19.6% increase in fracture toughness) compared to those of the pure WC specimen. The fiber porosity improved the second phase‐WC matrix microstructural combination. The described approach is a novel preparation method for the WC composites. Furthermore, a new toughening mechanism, which is based on "pinning and stretching", was determined. These findings suggest that porous boron nitride fibers can be considered to be second phases for toughening the WC composites.